Crust and subduction zone structure of Southwestern Mexico. Issue 2 (11th February 2015) - Suhardja, Sandy Kurniawan; Grand, Stephen P.; Wilson, David; Guzman‐Speziale, Marco; Gomez‐Gonzalez, Juan Martin; Dominguez‐Reyes, Tonatiuh; Ni, James
Abstract: Southwestern Mexico is a region of complex active tectonics with subduction of the young Rivera and Cocos plates to the south and widespread magmatism and rifting in the continental interior. Here we use receiver function analysis on data recorded by a 50 station temporary deployment of seismometers known as the MARS (MApping the Rivera Subduction zone) array to investigate crustal structure as well as the nature of the subduction interface near the coast. The array was deployed in the Mexican states of Jalisco, Colima, and Michoacan. Crustal thickness varies from 20 km near the coast to 42 km in the continental interior. The Rivera plate has steeper dip than the Cocos plate and is also deeper along the coast than previous estimates have shown. Inland, there is not a correlation between the thickness of the crust and topography indicating that the high topography in northern Jalisco and Michoacan is likely supported by buoyant mantle. High crustal Vp / Vs ratios (greater than 1.82) are found beneath the trenchward edge of magmatism including below the Central Jalisco Volcanic Lineament and the Michoacan‐Guanajuato Volcanic Field implying a new arc is forming closer to the trench than the Trans Mexican Volcanic Belt. Elsewhere in the region, crustal Vp / Vs ratios are normal. The subducting Rivera and Cocos plates are marked by a dipping shear wave low‐velocity layer. We estimate the thickness of the low‐velocity layer to be 3 to 4 km with an unusually high Vp / Vs ratio of 2.0 to 2.1 and a drop in S velocity of 25%. We postulate that the low‐velocity zone is the upper oceanic crust with high pore pressures. The low‐velocity zone ends from 45 to 50 km depth and likely marks the basalt to eclogite transition. Key Points: Geometry of Rivera and Cocos plate from crustal study High Vp / Vs ratio beneath trenchward edge of magmatism Low shear velocity layer on top subduction plate